Comparison between Alpha and Calendula for Healing of Third-Degree Burn in Rats: Burn healing in rat by Alpha and Calendula - Nader Tanideh; Milad Yavari; Anahita Seddighi; Omid Koohi Hosseinabadi; Melika Farshad; Maral Mokhtari; Babak Shirazi Yeganeh; Akram Jamshidzadeh; Sajad Daneshi; Behrouz Nikahval (Iranian Journal of Pharmaceutical Sciences, 2017)
In this study, we compared the effects of Calendula and Alpha ointment in the treatment of burn wounds and also compared its results with silver sulfadiazine (SSD). Seventy-five male Sprague-Dawley rats were divided into five groups, and similar burn ulcers were produced on anterior surface of thigh of rats. In the first group of rats no treatment was applied, base gel was applied topically to group II, in groups III-V, Alpha, SSD, and Calendula preparations were applied, respectively. Wound healing, contraction, and histopathological evaluation were evaluated at the end of 7, 14, and 21 days. Alpha ointment was equally effective as Calendula gel, and had better efficacy compared to SSD for all markers of wound healing at days of 7, 14, and 21.Alpha and Calendula preparations are less expensive drugs and significantly improve the quality of wound healing and scar formation and are more appropriate treatment choices than SSD. Therefore, we recommended them as alternative to SSD, especially in patients with low economical backgrounds or in those who show adverse reactions to SSD.